Verticality, urbanization, and touristification in the Andes: the case of Huaraz, Peru - Branca, Domenico (2022)
Mountain cities specializing in tourism increasingly aim at valorizing cultural and natural heritage to compete for global attention. In this context, the postmodern urbanization of mountains plays a decisive role: driven by touristification processes, it alters the sociospatial and economic configuration of mountain cities and their hinterlands, which are becoming vertically arranged “operational landscapes”, and profoundly changes city–mountain interactions. To foster sustainable development in urbanizing mountain destinations, it is crucial to understand these settlements’ embeddedness in both (1) nature and culture and (2) space and time. The Andean city of Huaraz is a case in point: an intermediate center in highland Peru, it is characterized by a strategic location in the Callejón de Huaylas (Santa Valley), influenced by Hispanic and Quechua culture and dominated by the glaciers of the Cordillera Blanca. Combining (1) a theoretical framework that considers planetary urbanization, touristification and vertical complementarity and (2) a case study technique inspired by urban environmental profiles, we trace the development of the city–mountain relation in Huaraz, focusing on the way in which the material and non-material dimensions of the surrounding mountains influence urban development. We conclude with a call for overcoming a set of three persisting dichotomies that continue to impair sustainable development.